Panniculitis as first manifestation of disseminated cryptococcosis - Verónica Rotela; Fátima Agüero; Beatriz Di Martino Ortiz; Mirtha Rodriguez; Oilda Knopfelmacher; Lourdes Bolla (Our Dermatology Online, 2017)
Cryptococcosis is an opportunistic fungal infection caused by Cryptococcus neoformans. Encapsulated yeast worldwide distribution, related to pigeon droppings, its main entrance is inhaled. Asymptomatic in immunocompetent, but produces exceptionally pneumonitis and a skin primoinfection. In immunocompromised individuals, it spreads through the blood mainly affecting the central nervous system, skin and bones. We report the case of a 23-year-old woman, veterinary student, chronic insufficient kidney by diffuse glomerulosclerosis of unknown etiology for 2 years, Hypertension and anemia of chronic diseases treated with prednisone, cyclophosphamide boluses monthly, and tri-weekly hemodialysis; with violet-erythematous nodules on legs and right arm, showing oval birefringent structures, intracytoplasmic PAS positive, yeast, encapsulated, surrounded by a clear halo around a core biopsy of hypodermis, and skin culture positive for Cryptococcus neoformans. Treatment was established with fluconazole 400 mg/d for two weeks, then 200mg/d as crops, with a resolution of skin lesions. Not detected until 12 months of follow-up by Cryptococcus neoformans invasion in other organs.